2015
DOI: 10.1155/2015/756976
|View full text |Cite
|
Sign up to set email alerts
|

Untypical Amlodipine-Induced Gingival Hyperplasia

Abstract: Amlodipine is a third generation dihydropyridine calcium channel blocker that is frequently used in therapy of hypertension. Among many side effects, amlodipine has been found associated with gingival overgrowth (GO) which usually occurs within the first three months of starting therapy at a dose of 10 mg/day. However, there are very few reports on amlodipine-induced gingival overgrowth (AIGO) at a lower dose (5 mg/day) and only after short term administration. A 64-year-old male patient with hypertension, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Amlodipine is a third generation relatively newer of calcium channel blockers that is frequently used in therapy of hypertension, exhibit adverse effect of gingival enlargement in middle to older aged adults 29,30 . Valsartan is angiotensin receptor blocker used in therapy of hypertension but with no side-effects observed with these calcium channel blockers 31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amlodipine is a third generation relatively newer of calcium channel blockers that is frequently used in therapy of hypertension, exhibit adverse effect of gingival enlargement in middle to older aged adults 29,30 . Valsartan is angiotensin receptor blocker used in therapy of hypertension but with no side-effects observed with these calcium channel blockers 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the gingival index between the two groups. The increases of Amlodipine may be due to that Amlodipine exhibit adverse effect of gingival enlargement in middle to older aged adults 29,30 , but this increase is non-significant, which may be due to lower dose of Amlodipine (5 mg/day) and these results are in agreement with Seymour et al reported that gingival hyperplasia could be a side effect of amlodipine even with a very short term and low dose administration 40 , or may be due to sharp oral hygiene instruction these is agreed with Thompson et al and Prisant and Herman , where they say drug-induced gingival enlargement can be minimized, but not prevented by meticulous oral hygiene, and regular recall 26,41 .…”
Section: Discussionmentioning
confidence: 99%
“…A gingivahyperplasia előfordulási gyakorisága összefügg a farmakokinetikai tényezőkkel, de a kórkép súlyossága nem [10,14]. A kórkép kialakulása ezenkívül függ a gyógyszeres terápia időtartamától, a páciens nemétől, korától, genetikai tényezőktől és a páciens szájhigiéniájától [15][16][17]. A kalciumcsatorna-blokkoló által indukált gingivamegnagyobbodás a dohányosok körében jóval markánsabb előfordulást mutat [17].…”
Section: áBraunclassified
“…Gingival overgrowth is a kind of painless condition, regarded as enormous enlargement of the inter dental papillae, which can vary from mild to extremely severe pain and can be accompanied by swelling of the gingival margin. 1 Gingival overgrowth possess a great concern to the physicians and the patients as it is a potential cosmetic problem and a medium for the development of micro organisms. More than 20 drugs are reported to produce the gingival overgrowth as of now.…”
Section: Introductionmentioning
confidence: 99%